2013
DOI: 10.1007/s10695-013-9812-8
|View full text |Cite
|
Sign up to set email alerts
|

Pro-oxidant and antioxidant responses in the liver and kidney of wild Goodea gracilis and their relation with halomethanes bioactivation

Abstract: In mammals, it has been shown that halomethanes (HM) are bioactivated by enzymes such as CYP 2E1 and the theta isoform of GST to produce reactive metabolites. However, in fish, little information is available, although HM can form autochthonously in aquatic environments. This study assessed the effect of HM in dusky splitfin (Goodea gracilis) from three lakes of the Valley of Mexico by analysing specific HM biomarkers as well as a broad range of biomarkers. The concentration of HM was a function of its half-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 41 publications
0
7
0
3
Order By: Relevance
“…Results indicate that the order of DNA‐damaging potency is: BDCM > DBCM > bromoform > chloroform. Metabolism by cytochrome P450 seems to proceed mainly through the CYP2E1 isoform, resulting in the production of reactive intermediates and reactive oxygen species (ROS) (Porubsky et al, ) in laboratory rodents (Seth et al, ) and fish (Vega‐Lopez et al, ; Olivares‐Rubio et al, ). Oxidative stress induces significant cellular injury at various levels, including lipid peroxidation and oxidative DNA damage.…”
Section: Introductionmentioning
confidence: 99%
“…Results indicate that the order of DNA‐damaging potency is: BDCM > DBCM > bromoform > chloroform. Metabolism by cytochrome P450 seems to proceed mainly through the CYP2E1 isoform, resulting in the production of reactive intermediates and reactive oxygen species (ROS) (Porubsky et al, ) in laboratory rodents (Seth et al, ) and fish (Vega‐Lopez et al, ; Olivares‐Rubio et al, ). Oxidative stress induces significant cellular injury at various levels, including lipid peroxidation and oxidative DNA damage.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, in specimens of dusky splitfin exposed to CHCl 3 levels of RC=O were above controls (p<0.05 and p<0.01; Figure 3E). In some water bodies, the renal content of RC=O in G. gracilis was below controls (Olivares-Rubio et al, 2013), as it was also observed in fishes exposed to CH (Thomas et al, 1990) o por reacciones radicalarias es factible la formación de polímeros con baja actividad biológica (Gregus, 2008 • is a defense mechanism in the innate immunity. Similar results were found in the liver of G. gracilis exposed in the same conditions in this study (Dzul-Caamal et al, 2013).…”
Section: Oxidative Damage (Rooh Sratb and Rc=o)mentioning
confidence: 78%
“…Juveniles of indistinct sex aged eight months (50.40±0.65 mm and 0.94±0.06 g) in non-reproductive state born in the lab were used for the tests. orgánica y precursores de HM (Vega-López et al, 2012;Olivares-Rubio et al, 2013). En el hígado y el riñón de G. gracilis "habitante de tres lagos del centro de México" se encontró que la presencia de HM fue capaz de inhibir la respuesta metabólica de estos peces , lo que sugiere la generación de metabolitos reactivos (Parkinson y Ogilvie, 2008) particularmente los derivados de la GST isoforma tetha.…”
Section: Species Under Study and Experimental Proceduresunclassified
See 2 more Smart Citations